Exploration and morphological characterization of Trichoderma spp from organic waste at TPST Rempoah-Baturraden, Banyumas Regency - Muljowati Juni Safitri; Oedjijono Oedjijono; Dewi Ratna Stia; Mariana Afifah; Chemeltorit Philip (E3S Web of Conferences)
Members of the Trichoderma genera are able to adapt to various habitats including organic waste, with a fairly high population density. This study aimed to determine the differences in the morphological characteristics of Trichoderma spp isolated from the Rempoah Integrated Waste Processing Facility (TPST), Baturraden District, Banyumas Regency. The experiment was conducted at the Mycology and Phytopathology Laboratory, Faculty of Biology, Jenderal Soedirman University. The results of the exploration of the Trichoderma genera obtained three isolates. The characteristics observed were macroscopic characteristics including the colour and shape of the colonies, and microscopic characteristics including the shape of conidiophores, phialides, and conidia. The results showed that the three Trichoderma isolates from Rempoah TPST had different morphological characteristics. The species of Trichoderma spp obtained were T. koningii, T. asperellum, and T. harzianum.